Soundscape and ecology : data collection to an urban soundwalk - Rocha, Mariana Salgueiro (2022)
Sound is an immensely important aspect of our perception and daily life, by which we are constantly surrounded. From the perception of space to the relationships with other elements or human beings, sound is always present. In this thesis the main focus is the urban soundscape, its relationships with ecology and to the act of listening in a soundwalk. Our starting point was an analysis of what we considered to be the key concepts, such as the concept of soundscape and ecology, the act of listening in an individual and collective sense, and the one of soundwalks as a tool for ecological awareness. These concepts, more specifically soundscape and soundwalk, are of extreme importance since they are key concepts to the understanding of our relationship with sound on our daily life. The first relates to the sounds that surround our daily life, and the latter the exploration of said sounds. These concepts are part of the analysis that is the basis to the development of our research. Then we gathered data from the academic community about their emotional relationship with the city, namely relating to the urban soundscape. This part of the research was integrated in a financed research project - HAC4CG. After the collection, the data was analyzed in a compiling and organizing way and then in light of the concepts mentioned above. The analyzed data informed the creation of soundwalks. As mentioned, part of the present thesis is integrated in the research project HAC4CG – Heritage, Art, Creation for Climate Change. Living the city: catalysing spaces for learning, creation and action towards climate change, funded by FCT (Fundação para a Ciência e Tecnologia) and co-funded by FEDER (Fundo Europeu de Desenvolvimento Regional). This Work Line - Engaging citizens through art, intends to create new routes for the city of Porto, based on a collection of data related to climate change, the city, and its heritage. Our role in the mentioned project is of research fellow, from January to December of the present year.